Hair tourniquet syndrome of labia minora in 14 year teen: a rare case report - Nutan, Kumari; Jain, Ajay Kumar (International Journal of Research in Medical Sciences, 2020)
Hair tourniquet syndrome (HTS) is rare clinical phenomenon in which body appendage is circumferentially entangled by string of hair leading to ischemia and necrosis or even autoamputation of the appendage. HTS commonly affects toes, finger or genitalia. Early diagnosis and prompt intervention lead to good outcome. This article presents a case of hair tourniquet syndrome of labia minora, a rare presentation in 14 year child.